ANALISIS KELAYAKAN FINANSIAL PADA PEMBANGUNAN PERUMAHAN LIPPO KARAWACI DI KABUPATEN TANGGERANG: Studi Kasus Menggunakan Metode Net Present Value (NPV), Internal Rate of Return (IRR), dan Payback Period. - nur pauji, zulpa; Maskur, Atep; Hartati, Gini (Jurnal Ilmiah Teknik Sipil, 2026)
This research aims to analyze the financial feasibility of the Lippo Karawaci housing project in Tanggerang Regency. Feasibility analysis uses several investment indicators, namely Net Present Value, Internal Rate of Return, and Payback Period. The research method applied is descriptive quantitative with a case study approach, where financial data is assessed based on cash flow projections. The calculation results of the investment feasibility indicators show a positive value and meet the eligibility criteria. Positive Net Present Value of IDR 50,133,020,631, Internal Rate of Return of 15.63% exceeding the discount rate of 10%, and a Payback Period of 5 years which shows that the investment capital can be recovered before the project ends in 2029. Based on these three indicators, the Lippo Karawaci housing project is declared financially feasible. These findings confirm that the project is a prospective investment with a profitable rate of return. However, this research is only limited to the financial aspect. Future research is recommended to combine non-financial feasibility analysis and sensitivity scenarios to provide more comprehensive and realistic results. This research contributes to the field of civil engineering by offering empirical evidence regarding methods for assessing financial feasibility in housing development projects.